Mixed research tools for thermal comfort studies of medium density mass housing - Mohd Ariffin, Noor Aziah (2014)
This paper describes the methodology used in the investigation of thermal comfort studies with the notion that energy efficient design adapted to double-storey terraced houses in Malaysia can increase thermal comfort and decrease energy consumption. The study requires a method of exploring the thermal performance of existing and hypothetical dwellings. Hence, the paper aims to determine that, if from the outset, houses are designed by taking into consideration energy efficient design strategies; in this case, orientation studies and the utilisation of passive design features, the result will be dwellings with lower internal temperatures and thus, lower energy consumption. Utilising three different methods of investigations: the questionnaire survey, temperature survey and computer simulation to corroborate findings from each, this paper describes the process undertaken. The triangulation of the mixed methods validated the findings to the problems identified in this study indicating increment of thermal comfort and reduction of energy consumption.